2012
DOI: 10.1158/0008-5472.can-12-0465
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Soluble Leptin Receptor in Risk of Colorectal Cancer in the European Prospective Investigation into Cancer and Nutrition Cohort

Abstract: Leptin, a peptide hormone produced primarily by the adipocytes, is hypothesized to play a role in the pathogenesis of colorectal cancer (CRC). Soluble leptin receptor (sOB-R) may regulate leptin's physiologic functions; however its relation to CRC risk is unknown. This study explored the association of leptin and sOB-R with risk of CRC in a prospective nested case-control study within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. A total of 1,129 incident CRC cases (713 colon,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 52 publications
4
60
1
1
Order By: Relevance
“…In a prospective study from Sweden, higher circulating leptin was associated with higher risk of colon cancer in men but not in women [71]. Similarly, in EPIC pre-diagnostic leptin was associated with higher colon cancer risk only in men, while in women no association was observed [72]. A positive positive association between pre-diagnostic circulating leptin concentrations and risk of colon cancer in men was also observed in a study from Norway [73].…”
Section: Leptinmentioning
confidence: 73%
See 1 more Smart Citation
“…In a prospective study from Sweden, higher circulating leptin was associated with higher risk of colon cancer in men but not in women [71]. Similarly, in EPIC pre-diagnostic leptin was associated with higher colon cancer risk only in men, while in women no association was observed [72]. A positive positive association between pre-diagnostic circulating leptin concentrations and risk of colon cancer in men was also observed in a study from Norway [73].…”
Section: Leptinmentioning
confidence: 73%
“…In a meta-analysis including six prospective studies, higher leptin concentrations were significantly associated with higher risk of colorectal cancer [76]. Interestingly, soluble leptin receptor (sOB-R), which determines the bioactivity of leptin, was strongly inversely associated with risk of colorectal cancer in EPIC [72]. In two US cohorts soluble leptin receptor was not associated with higher overall colorectal cancer risk in either men or women, although high sOB-R concentrations were associated with higher rectal cancer risk in women [56].…”
Section: Leptinmentioning
confidence: 99%
“…The level of leptin or ObRb has been found to be associated with an increased risk of CRC, although some study revealed a normal level of leptin in the serum of patients with CRC (Aleksandrova et al, 2012;Aloulou et al, 2008). A recent study (with 3,614 CRC vs 1,215 CRA vs 5,220 controls) found a positive association between serum leptin and the CRA risk, but not with the CRC risk (Gialamas et al, 2013).…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%
“…A growing body of evidence indicates that the metabolic syndrome (MetS) and expression of various adipokines (leptin and adiponectin) associated with obesity plays a crucial role in the development of colorectal cancer (Hardwick et al, 2001;Hoda et al, 2007;Endo et al, 2011;Aleksandrova et al, 2012;Healy et al, 2012;Erkasap et al, 2013;Gialamas et al, 2013). In obese people, the elevated insulin level, the rapidly growing secretion of leptin, and decreased adiponectin levels altogether activate several signaling pathways that favor carcinogenesis and are associated with colon cancer development.…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%
See 1 more Smart Citation